Comparison between silicon and single-crystal diamond photodiodes for localized pulsed fast neutron detection. (15th May 2018) - Verona, C.; Verona-Rinati, G.; Platt, S.; Schooneveld, E. M.; Pietropaolo, A.
Abstract: Experimental measurements are presented, devoted to the cross-comparison of two small-size fast neutron detection devices, namely Single-Crystal Diamond diode (SCDD) and Silicon Photodiode (SiPD). Neutron time-of-flight spectra are simultaneously recorded under the same experimental conditions, using an array composed of two SCDDs and two SiPDs placed in the incident beam of the ROTAX beam line at the ISIS spallation neutron source (UK). Experimental spectra are compared to calculated ones, obtained by taking into account material characteristics and the neutron spectrum. The SCDD detector features a higher time resolution with respect to the SiPD, likely related to the different neutron cross-sections and the electronic thresholds set during the measurements.